Authentic Assesment of The Lesson Planning Accomplished by The Indonesian Language and Literary Teachers in Bogor Secondary Schools - Suhendra ,; Rina Rosdiana; Stella Talitha (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
Teachers are an significant element in the development of assessment instruments. Assessing is, therefore, one of the competencies that must be possessed by teachers . The teacher's understanding of the assessment can be reflected in the assessment presentation on the Lesson Plans (RPP). This study examines the preparation of authentic assessment of the even semester Lesson Plan in the Indonesian language curriculum at five high schools in Bogor. The applied method in this research is qualitatively descriptive research. The purpose of this study is to describe 1) the accuracy of the formulation of the problem with the basic competence and indicator, 2) the completeness of the assessment instrument, and 3) the selection of assessment type. The results showed that 90.9% BC or indicator evaluation instrument is made while 9.1% is not made. This causes the teacher unable to know the level of students' understanding of the BC. Ninety percents (90%) of instrument evaluation is less precise; while 10 % of the evaluation instrument is less precise, less appropriate. Forty ( 40 %) of evaluation instruments are complete and 60% are incomplete (no scoring guidelines and answer keys). There are seven development forms of authentic assessment, namely performance appraisal, project appraisal, portfolio assessment, written assessment, attitude assessment, self-assessment, and product assessment. Here is an overview of the authentic assessment form used by teachers. 20% of all indicators are studied, in the form of performance appraisals, the type is the oral practice . Meanwhile, 80% is a written assessment, in the form of multiple choice test and description (short field and essay). This shows that most teachers do not take advantage of other forms of authentic assessment. Keywords: authentic assessment, basic competencies, indicators.